The Genealogical Construction of the Kyrgyz Republic : Kinship, State and 'Tribalism'. - Gullette, David (BRILL, 2010)
This book explores the conceptions of genealogy, kinship and 'tribalism' in the intertwined construction of personhood and national identity in the Kyrgyz Republic. It makes an important contribution to several theoretical and regional debates.